Production data of wine grape gene bank (Vitis spp.) of University of Debrecen, east Hungary - Rakonczás, N. (International Journal of Horticultural Science, 2019)
National wine strategy of Hungary promotes the use of “flexible” grape cultivars. These enable producers’ best fit to wine market changes and expectations. This study is aimed to present data on the gene bank of the University of Debrecen, Hungary. Data were collected at a single site, between 2010 and 2018 in east Hungary lowland on acidic sandy soil, own rooted planting material. Our results showed that besides high yield and adequate cane production desired sugar content at convenient pH is to be awaited with moderate deviation between vintages. Presented concept demonstrate technological flexibility of cultivars by their average deviation from regression equation between increasing sugar and pH typical for the vintage composed of data of cultivars of the gene bank. Average positive deviation means higher sugar content at specific pH, thus higher sugar content at desired, conveniently low pH (3.0-3.2 pH).